Understanding leisure - Kew, Frank; Bramham, Peter; Haywood, Les (Stanley Thornes, 1995)
"The ideal introduction to the study of leisure, the industry and those who enjoy it. It provides full discussion of the key issues, and includes exercises and discussion topics at the end of chapters to consolidate learning plus excellent guides to further reading. The new edition has been carefully revised to take account of recent developments such as the National Lottery."--BOOK JACKET.